Importing genetically altered animals: ensuring quality - M.-C. Birling; M. D. Fray; P. Kasparek; J. Kopkanova; M. Massimi; R. Matteoni; L. Montoliu; L. M. J. Nutter; M. Raspa; J. Rozman; E. J. Ryder; F. Scavizzi; et al. (Mammalian Genome, 2022)
The reproducibility of research using laboratory animals requires reliable management of their quality, in particular of their genetics, health and environment, all of which contribute to their phenotypes. The point at which these biological materials are transferred between researchers is particularly sensitive, as it may result in a loss of integrity of the animals and/or their documentation. Here, we describe the various aspects of laboratory animal quality that should be confirmed when sharing rodent research models. We also discuss how repositories of biological materials support the scientific community to ensure the continuity of the quality of laboratory animals. Both the concept of quality and the role of repositories themselves extend to all exchanges of biological materials and all networks that support the sharing of these reagents.